Xanthones of Garcinia cowa - na Pattalung P. (2014)
Five xanthones have been isolated from Garcinia cowa Roxb. (Guttiferae): cowanin (1), cowanol (2), cowaxanthone (3), 1,3,6-trihydroxy-7-methoxy- 2-5-bis(3-methyl-2-butenyl)xanthone (4), and norcowanin (5). The structures were assigned by spectroscopic studies. Xanthones 2 and 3 showed moderate antimicrobial activity against Staphylococcus aureus.